Architecture, politics, & identity in divided Berlin - Pugh, Emily (Culture, politics, and the built environment, 2014)
"Emily Pugh provides an original comparative analysis of selected works of architecture and urban planning in East and West Berlin during the 'Wall era,' to reveal the importance of these structures to the formation of political, cultural, and social identities"..